Vowel constrictions are recoverable from formants - Iskarous, Khalil (2010)
The area function of the vocal tract in all of its spatial detail is not directly computable from the speech signal. But is partial, yet phonetically distinctive, information about articulation recoverable from the acoustic signal that arrives at the listener’s ear? The answer to this question is important for phonetics, because various theories of speech perception predict different answers. Some theories assume that recovery of articulatory information must be possible, while others assume that it is impossible. However, neither type of theory provides firm evidence showing that distinctive articulatory information is or is not extractable from the acoustic signal. The present study focuses on vowel gestures and examines whether linguistically significant information, such as the constriction location, constriction degree, and rounding, is contained in the speech signal, and whether such information is recoverable from formant parameters. Perturbation theory and linear prediction were combined, in a manner similar to that in Mokhtari (1998) [Mokhtari, P. (1998). An acoustic-phonetic and articulatory study of speech-speaker dichotomy. Doctoral dissertation, University of New South Wales], to assess the accuracy of recovery of information about vowel constrictions. Distinctive constriction information estimated from the speech signal for ten American English vowels were compared to the constriction information derived from simultaneously collected X-ray microbeam articulatory data for 39 speakers [Westbury (1994). Xray microbeam speech production database user’s handbook. University of Wisconsin, Madison, WI]. The recovery of distinctive articulatory information relies on a novel technique that uses formant frequencies and amplitudes, and does not depend on a principal components analysis of the articulatory data, as do most other inversion techniques. These results provide evidence that distinctive articulatory information for vowels can be recovered from the acoustic signal.